2007
DOI: 10.1093/jos/ffm011
|View full text |Cite
|
Sign up to set email alerts
|

Processing Presupposed Content

Abstract: This paper presents two experimental studies investigating the processing of presupposed content. Both studies employ the German additive particle auch (too). In the first study, participants were given a questionnaire containing bi-clausal, ambiguous sentences with 'auch' in the second clause. The presupposition introduced by auch was only satisfied on one of the two readings of the sentence, and this reading corresponded to a syntactically dispreferred parse of the sentence. The prospect of having the auch-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
1
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(51 citation statements)
references
References 26 publications
6
43
1
1
Order By: Relevance
“…Geurts et al 2010) and presuppositions (e.g. Schwarz 2007, Beaver & Clark 2008, Chemla 2009, where a common paradigm is to ask linguistically untrained participants to assess whether an utterance has a particular implication or which of a given set of implications an utterance has.…”
Section: Introduction: Projective Content As a Domain For Crosslinguimentioning
confidence: 99%
“…Geurts et al 2010) and presuppositions (e.g. Schwarz 2007, Beaver & Clark 2008, Chemla 2009, where a common paradigm is to ask linguistically untrained participants to assess whether an utterance has a particular implication or which of a given set of implications an utterance has.…”
Section: Introduction: Projective Content As a Domain For Crosslinguimentioning
confidence: 99%
“…Although theoretical discussions of presuppositions have gone on for decades, it is only recently that language researchers have begun to investigate the on-line processing of presuppositions (e.g., Chemla & Bott, 2013;Schwarz, 2007; Singh et al., in press;Tiemann et al, 2015). For example, some self-paced reading studies showed that presuppositions are available rapidly to the comprehenders (Tiemann et al, 2011Schwarz, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For example, some self-paced reading studies showed that presuppositions are available rapidly to the comprehenders (Tiemann et al, 2011Schwarz, 2007). Tiemann and colleagues (2011) reported a delay in the reading of presupposition trigger words compared to non-presupposition controls.…”
Section: Introductionmentioning
confidence: 99%
“…Standard reading measures were calculated for purposes of analysis. Based on prior self-paced reading experiments using the same general approach (Schwarz 2007, Tiemann et al 2011), we expect increases in reading time when sentences are presented in contexts that are inconsistent with the presupposition. The time point at which such increases arise is indicative of the relevant presupposition having been computed at this point.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the general notion that presuppositions require some form of contextual support, previous experimental studies have found that lack of such support is reflected in various processing effects, e.g. regarding the choice of interpretation of a syntactically ambiguous structure and increase in reading times (Schwarz 2007) or the need for accommodation (Tiemann et al 2011; see also , and Chemla and Bott 2010 for other recent experimental studies). In a reading study using eye tracking, we investigated two issues concerning the processing of presuppositions.…”
Section: Introductionmentioning
confidence: 99%